Development and pre-clinical evaluation of a Zika virus diagnostic for low resource settings - Balea, Rickyle; Pollak, Nina M.; Hobson-Peters, Jody; Macdonald, Joanne; McMillan, David J. (Frontiers in Microbiology, 2023)
Introduction Zika virus (ZIKV) is a re-emerging flavivirus that poses a significant public health threat. ZIKV exhibits a wide array of non-vector borne human transmission routes, such as sexual transmission, transplacental transmission and blood transfusion. Detection and surveillance of ZIKV is considered paramount in prevention of major outbreaks. With the majority of cases reported in low-resource locations, simple, low-cost detection methods are considered highly desirable. Materials and Methods Here we have developed a sensitive and specific ZIKV diagnostic using reverse transcription recombinase-aided amplification (RT-RAA) coupled with lateral flow detection (LFD) targeting a highly conserved region of the ZIKV NS1 gene. Results We show our rapid, isothermal-ZIKV-diagnostic (Iso-ZIKV-Dx) can detect 500 copies of synthetic ZIKV RNA/μL in under 30 min at a constant 39°C. Using simulated urine samples, we observed that Iso-ZIKV-Dx also detects as low as 34.28 RNA copies/reaction of ZIKV (MR766 strain). Specificity testing confirmed that our test does not detect any co-circulating flaviviruses (dengue, West Nile, Japanese encephalitis, Murray Valley encephalitis and yellow fever viruses) or chikungunya virus. Sample processing results show complete inactivation of ZIKV (MR766 strain) in 5 min at room temperature using our novel viral RNA sample preparation reagent. Furthermore, lateral flow strips testing demonstrates positive diagnoses in as little as 5 min in running buffer. Discussion Contrary to conventional RT-qPCR, our Iso-ZIKV-Dx does not require expensive machinery, specialised laboratory settings or extensively trained personnel. Pre-clinical evaluation demonstrates that our test exhibits robust, in-field capabilities without compromising sensitivity or specificity. When compared to the gold-standard RT-qPCR, our Iso-ZIKV-Dx test offers an array of applications that extend beyond diagnostics alone, including potential for surveillance and monitoring of ZIKV vector competency.